Injuries of the upper extremities for individual and team games according to (types, areas of occurrence, causes, severity)For the players of Al-Qadisiyah Governorate - عماد عزيز نشمي, AZEZ NASHMIE (Mustansiriyah Journal of Sports Science, 2024)
Sports medicine is one of the sciences that serve sports in general by preserving the health and safety of the player and preventing and limiting the occurrence of injury to ensure that the player continues to practice sports activity, in addition to the necessity to rehabilitate the athlete and his return to the stadiums at the same level. The competition between the players and the teams leads to the occurrence of injuries and their increase day after day, and the importance of dealing with the upper limb in its parts for research comes to the fore. And the most frequent injuries, the causes and areas of their occurrence, and their severity as a phenomenon that deserves study, the preventive foundations, how injuries occur, and the method of immediate treatment, in a way that can represent a simple contribution to the process of advancing sports levels and achieving the sports goals envisaged by preparing and training athletes.The aim of the research is to identify the most common injuries that affect the upper extremity in individual and team sports, and to identify the rates and types of injuries in different sports, according to the specificity of each game. The researchers used the descriptive survey method for its suitability to the nature of the research. And the difference in the clubs of Al-Qadisiyah Governorate for the sports season (2021-2022) and those who visited the (Physiotherapy Center in Al-Diwaniyah Teaching Hospital), with a total number of 212 injured, while the research sample was only 180 injured.The researchers concluded that the muscle rupture injury is one of the most common injuries in the upper extremity among the players of Al-Qadisiyah Governorate, while the blister injury was one of the least visible injuries when compared with other sports injuries. its regions.The researchers recommended not to overexertion in training and give complete rest to the athletes during and after training and try to reduce friction with the opponent by avoiding harassment that occurs with the other competing team and focus on a good warm-up before starting exercises and competitions to avoid the occurrence of sports injury and focus on warming up the homers, shoulder and hand. And his joint, which was the most exposed injury.